Study on the Influence of Hall Effect on the Performance of Disk Generation Channel - Linyong Li; Guang Wang; Yingke Liao; Qing Wu; Peijie Ning (Magnetochemistry)
Compared to the Faraday-type power generation channel structure, the disk-type power generation channel offers several advantages, including a simpler structure, higher enthalpy extraction efficiency, and greater power density. These features effectively reduce the requirements for magnetic systems, making it a priority development direction for space nuclear magnetohydrodynamic (MHD) power generation channels. The disk power generation channel utilizes the Hall effect for power generation; however, the impact of the Hall effect on current distribution, plasma characteristics, conductivity, and other parameters within the disk-type power generation channel remains unclear. A mathematical model of a plasma MHD power generation channel was established using a He/Xe mixed gas as the working fluid. Numerical simulations were conducted to investigate the performance of the disk-shaped power generation channel under varying Hall parameters. The research findings indicate that a strong circular Faraday current forms near the anode, leading to significant anode erosion. The Hall effect significantly influences plasma stability, with stronger Hall effects resulting in reduced plasma stability. Conductivity between the electrodes gradually increases from the anode to the cathode, becoming more pronounced as the Hall effect intensifies. By enhancing the Hall effect, the enthalpy extraction rate is significantly improved, electrical efficiency asymptotically approaches 50%, and the overall performance of the power generation channel is substantially enhanced.